The administrative Problems Faced by the Principals of the Schools of the First Cycle of Basic Education from their Point of view - A Field Study in the Tartous Province - Zreiki , Hyam; Mobayed, Mouhannad; Wannous, Mais (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The current research tackles the problems faced by the principals of the schools of the first cycle of basic education in Tartous Governorate. Differences in their views on the problems they face are attributed to the following variables (sex, educational qualifications). In order to achieve the objective of the research, the analytical descriptive method was used. The sample included (86) managers and directors in the schools of the first cycle of basic education in Lattakia governorate for the academic year 2018/2019. The questionnaire consisted of four areas, namely (teacher problems, curriculum problems, problems with pupils, problems with teaching aids and means). These criteria included 37 words. The reached several results, the most important of which: - The total degree of problems faced by the principals of the schools of the first cycle of basic education in Tartous province from their point of view came to a medium degree. - There were no statistically significant differences between the average estimation of the members of the research sample from the principals of the first cycle schools in the basic education stage on the problems they face according to the variable gender. - There are statistically significant differences between the average of the assessment of the members of the research sample from the principals of the first cycle schools from the basic education level on the problems they face according to the variable of scientific and educational qualification in favor of the university vacation campaign. The study also made several recommendations, including increasing the training courses for the principals of the first cycle schools of basic education, and providing the schools with the required educational techniques.